تمظهر الآخر في رواية "الدروب الوعرة " لمولود فرعون - بوهادف, محجوبة (كلية الأدب العربي والفنون, 2025)
تتناول هذه الدراسة تمظهر الآخر في رواية الدروب الوعرة لمولود فرعون، من خلال تتبع صورته وتمثلاته داخل النص السردي، وكيف أسهم في تشكيل وعي الأنا الجزائرية في ظل الواقع الاستعماري، كما سلطت الضوء على البعد الفلسفي لمفهوم الآخر، وعلى آليات الصراع بين الأنا والآخر في سياق ثقافي وتاريخي معقد. وقد خلصت الدراسة إلى أن الرواية تقدم نقدًا ضمنيًا للاستعمار وتوثق آثارَه النفسية والاجتماعية في الفرد الجزائري This study examines the manifestation of the Other in The Difficult Paths by Mouloud Feraoun, by tracing its image and representations within the narrative text and how it contributed to shaping the Algerian self-awareness under colonial reality. It also highlights the philosophical dimension of the concept of the Other and the mechanisms of conflict between the Self and the Other in a complex cultural and historical context. The study concludes that the novel offers an implicit critique of colonialism and documents its psychological and social impact on the Algerian individual.
Keywords: الآخر، الأنا، رواية الدروب الوعرة، مولود فرعون، الاستعمار، الهوية، الصراع; Other, Self, The Difficult Paths, Mouloud Feraoun, colonialism, identity, conflict